Pengembangan E-Modul Pembelajaran Seni Rupa Berbasis PjBL Menggunakan Sistem Blended Learning di Kelas IV Sekolah Dasar - Nirwana, Nurul Sinta; Desyandri, Desyandri (Universitas Negeri Padang, 2024)
This research aims to develop an e-module for Visual Arts education in primary schools that is reliable, feasible, and impactful. The study context encompasses the integration of information technology by educators in schools, shortcomings in creating engaging and interactive learning materials, and the absence of Project-Based Learning (PjBL) frameworks in electronic module design. Moreover, educational institutions have yet to implement learning methodologies that align with technological advancements, such as Blended Learning approaches. Employing a Research and Development (R&D) methodology based on the ADDIE model, the research findings reveal that the Visual Arts e-module for fourth-grade students attains a content validity of 95%, media validity of 81.25%, and language validity of 96%. In surveyed schools, teachers responded 97.5%, while students responded 97.1%. Notably, there is a significant enhancement in artwork outcomes and user-friendliness of the media, with an increase from 85.3% to 95.3%, signifying substantial achievement. Thus, the PjBL-centered e-module for Visual Arts education in fourth-grade primary schools is reliable, feasible, and impactful for educational purposes.